1993
DOI: 10.1051/gse:19930506
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate restricted maximum likelihood estimation of genetic parameters for growth, carcass and meat quality traits in French Large White and French Landrace pigs

Abstract: Summary -Genetic parameters of 7 traits measured in central test stations -average daily gain (ADG1), feed conversion ratio (FCR) and backfat thickness (ABT) measured on candidates for selection, and average daily gain (ADG2), dressing percentage (DP), estimated carcass lean content (ECLC) and meat quality index (MQI) 0,30; 0,6/,; 0,22; 0,52; 0,39; 0,60; 0,33 en race LW et 0,3l,; 0,56; 0,25; 0,l!6; 0,31; 0,68; 0,23

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
14
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 24 publications
13
14
0
2
Order By: Relevance
“…It can be noted that values were generally lower for body composition traits than for growth and feed intake traits. This indicates no significant genotype by sex interaction for these traits, as was reported previously for FCR between females and castrates (Smith & Ross 1965), for ADG between boars on one hand and castrates and females on the other hand (Ducos et al 1993) and for carcass BFT between females and castrates (Jonsson 1971). Only the genetic correlation of BFT between males and castrates and between males and females, respectively 0.65 ± 0.14 and 0.69 ± 0.20, might suggest the presence of genotype by sex interactions, as found by Smith & Ross (1965) and McKay & Rahnefeld (1986).…”
Section: Resultssupporting
confidence: 79%
“…It can be noted that values were generally lower for body composition traits than for growth and feed intake traits. This indicates no significant genotype by sex interaction for these traits, as was reported previously for FCR between females and castrates (Smith & Ross 1965), for ADG between boars on one hand and castrates and females on the other hand (Ducos et al 1993) and for carcass BFT between females and castrates (Jonsson 1971). Only the genetic correlation of BFT between males and castrates and between males and females, respectively 0.65 ± 0.14 and 0.69 ± 0.20, might suggest the presence of genotype by sex interactions, as found by Smith & Ross (1965) and McKay & Rahnefeld (1986).…”
Section: Resultssupporting
confidence: 79%
“…Pooled heritability estimate of 0.47 for back fat thickness was reported across Australian Y (Large White) and L performance-tested boars with feed ad libitum (McPhee et al 1979). Higher estimates of 0.56 and 0.64 for back fat thickness were obtained in French L and Y (Large White) (Ducos et al 1993). Furthermore, Hicks et al (1999) reported heritability estimates from a Japanese Large White population of 0.43 for ADG and 0.69 for back fat.…”
Section: Heritability Of Growth Traitsmentioning
confidence: 93%
“…The latter estimates were obtained by a multivariate derivative free REML program that is compatible with a wide variety of statistical models (Groeneveld, 1991, Ducos el al;1992, Bergfeld and Groeneveld;, Tixier-Boichard el al, 1992Bidanel el al, 1992;Groeneveld el al., 1992;Spilke el al, 1993;Ducos et al, 1993;Dietl el al, 1993;Brade and Groeneveld, 1993;Spilke and Groeneveld, 1994;Groeneveld, 1994a;Groeneveld, 1994b). With this package, residual and additive genetic covariance matrices could be estimated for all 5 traits simultaneously.…”
Section: Introductionmentioning
confidence: 92%